Long noncoding RNA AK039312 and AK079370 inhibits bone formation via miR-199b-5p. (January 2021) - Yin, Chong; Tian, Ye; Yu, Yang; Li, Dijie; Miao, Zhiping; Su, Peihong; Zhao, Yipu; Wang, Xue; Pei, Jiawei; Zhang, Kewen; Qian, Airong
Graphical abstract: Highlights: Identified LncRNA AK039312 and AK079370 that inhibited osteoblast differentiation and bone formation. AK039312 and AK079370 sequestered miR-199b-5p, thus inhibited osteoblast differentiation. The combination of AK039312 and AK079370 was more drastic than AK039312 or AK079370 alone. The mixture of si-AK039312 and si-AK079370 showed strong capability on rescuing osteoporosis. Abstract: Osteoporosis caused by aging and menopause had become an emerging threat to human health. The reduction of osteoblast differentiation has been considered to be an essential cause of osteoporosis. Osteoblast differentiation could be regulated by LncRNAs, and increasing evidences have proved that LncRNAs may be adopted as potential therapeutic targets for osteoporosis. However, reports on rescue effects of LncRNAs in vivo are relatively limited. In this study, two LncRNAs (AK039312 and AK079370) were screened as osteogenic related LncRNAs. Both AK039312 and AK079370 could inhibit osteoblast differentiation and bone formation through suppressing osteogenic transcription factors. This inhibitory effect was achieved via binding and sequestering miR-199b-5p, and enhanced GSK-3β which further inhibited wnt/β-catenin pathway. Moreover, the siRNAs of AK039312 and AK079370 significantly alleviated postmenopausal osteoporosis, and the combination of si-AK039312 and si-AK079370 was more efficient than applying one si-LncRNA alone. This study has provided new insights for the therapy of osteoporosis.